Risk factors for recurrent Clostridium difficile infection among patients in the Clinical Centre of Vojvodina, Serbia: a retrospective clinical trial - Kovačević, Nadica; Doder, Radoslava; Preveden, Tomislav; Pete, Maria (Vojnosanitetski pregled, 2021)
Background/Aim. In the last two decades the incidence of recurrent Clostridium difficile infection (CDI) has risen. The aim of this study was to determine the risk factors for the recurrent CDI among patients hospitalized with the initial CDI. Methods. We conducted a retrospective clinical trial at the Clinic for Infectious Diseases, Clinical Center of Vojvodina, Serbia, between January 2010 and January 2016. We enrolled 488 patients with the initial CDI who were treated with oral vancomycin (125 mg, 4 times per day) or oral metronidazole (400 mg, 3 times per day) for 10 days. After the completion of therapy, there was 60 days of the follow-up period for the assessment of the rates of relapse. To determine the risk factors for the CDI relapse, we compared the demographics, clinical and laboratory characteristics of the patients who had a relapse with the patients who had a stable clinical response. Results. Of the 488 cases, 29.09% recurred. The relapse occured in 22.72% patients who received vancomycin and in 36.60% patients treated with metronidazole (p = 0.038). A statistically significant effect on the CDI relapse had the comorbidities such as a malignancies (19.52% vs 8.82%, p = 0.023) and the postoperative CDI (25.67% vs 10.29%, p = 0.035), hipoalbuminemia (< 25 g/L) (70.27% vs 41.94%; p = 0.034) and the concomitant antibiotic therapy (50.67% vs 20.29%; p = 0.031). The persistence of C. difficile toxin in the stool at the end of treatment was registered in 22.32% of patients treated with metronidazole vs 9.09% of patients given vancomycin (p = 0.03). Conclusion. Our data suggest that the important risk factors for the CDI relapse are comorbidities (surgery within a month before developing CDI and malignancy), hipoalbuminemia (< 25g/L) and concomitant non-CDI antibiotics therapy. Vancomycin is more effective than metronidazole in the elimination of C. difficile toxins. The presence of C. difficile toxins in the stool after the successful completion of the initial CDI therapy does not affect significantly the occurrence of relapse.
Keywords: clostridium difficile; infection; recurrence; risk factors.